Handbook of antiblocking, release, and slip additives - Wypych, George (ChemTec Publishing, 2014)
This handbook, now in its third edition, is a comprehensive reference on the subject of antiblocking, release, and slip additives, which are of high industrial importance. These additives are used to alter the properties and performance of polymers, and improve the efficiency and cost of processing methods.